Amplifying unheard voices or fueling conflict? Exploring the impact of leader narcissism and workplace bullying in the tourism industry - Alaa M. S. Azazz; Ibrahim A. Elshaer; Mansour Abdullah Alyahya; Tamer Ahmed Abdulaziz; Walaa Moustafa Elwardany; Sameh Fayyad (Administrative Sciences, 2024)
The hospitality industry, well-known for its energetic and people-intensive nature, frequently depends on effective leadership to motivate teamwork and safeguard sustainable operational success. Nevertheless, leadership approaches may significantly influence workplace dynamics and leader narcissism appears to be a probable disruptor. This study explores the dual-edged influence of leader narcissism in the hospitality industry, specifically in determining employee unheard voice behavior and bullying in the workplace. While leader narcissism can amplify unheard voices by nurturing an environment where staff feel forced to speak up, it can also fuel workplace conflict by generating toxic interactions and advancing bullying in the workplace. This research utilized a self-administrated questionnaire, collecting data from employees in five-star hotels and category (A) tourism companies in Cairo, Egypt, from May to August 2024 through a convenience sampling technique. Of the 425 distributed questionnaires, 394 valid responses were received, and Smart PLS-3.0 was employed for hypothesis testing. The study's findings indicate that employee voice behavior positively influences workplace bullying. There exists a favorable correlation between employee voice behavior and leader narcissism. Moreover, leader narcissism is proven to have a positive relationship with workplace bullying. Leader narcissism was recognized as a mediating variable in the connection between employee voice behavior and workplace bullying. While previous research has investigated how these factors influence work-related outcomes in broader organizational settings, this study focuses on their implications in tourism and hospitality. Additionally, the study delves into how leader narcissism mediates the connection between employee voice behavior and workplace bullying in the tourism industry. By highlighting and exploring the complexities of leader narcissism and its influence on workplace interrelationships, this research paper may offer valuable insights for top managers, policymakers, and academics seeking to generate healthier and more productive workplace environments in the tourism industry.
Keywords: 350; employee unheard voice behavior; workplace bullying; leader narcissism; tourism; hospitality